All-Dielectric Metasurface-Based Quad-Beam Splitter in the Terahertz Regime - Boyang Lv; Chunmei Ouyang; Huifang Zhang; Quan Xu; Yanfeng Li; Xueqian Zhang; Zhen Tian; Jianqiang Gu; Liyuan Liu; Jiaguang Han; Weili Zhang (IEEE Photonics Journal)
Seeking the unprecedented ability of metasurfaces to manipulate terahertz waves in a desired manner has attracted increasing interest. We design and investigate a kind of multi-channel, polarization-dependent transmission-type dielectric metasurface-based terahertz beam splitter. It is numerically demonstrated that such metasurfaces can manipulate terahertz beam, and split it into four channels with alterable angles and orthogonal polarizations, under the linearly polarized incidence with both the x- and y–polarization components. The suggested regime may alleviate the shortage of advanced multifunctional devices and provide extra freedom for terahertz functional device design.